2015
DOI: 10.1007/s12603-015-0493-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcomes of total parenteral nutrition use in patients aged greater or less than 80 years of age

Abstract: These data suggest TPN use is safe in patients aged ≥ 80 years and advanced age alone should not preclude TPN use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The average age of adults receiving PN was 66 years, older than the mean age of the entire study population 10 . Another recent report of PN use found that 12.8% of adults receiving PN were 80 years of age or older with outcomes similar to those of their younger counterparts 11 …”
Section: Introductionmentioning
confidence: 86%
“…The average age of adults receiving PN was 66 years, older than the mean age of the entire study population 10 . Another recent report of PN use found that 12.8% of adults receiving PN were 80 years of age or older with outcomes similar to those of their younger counterparts 11 …”
Section: Introductionmentioning
confidence: 86%